1994
DOI: 10.1002/1097-0142(19940901)74:5<1584::aid-cncr2820740514>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Midkine and pleiotrophin expression in normal and malignant breast tissue

Abstract: Background. Some growth factors may promote tumor growth by affecting tumor angiogenesis. The angiogenic growth factor, pleiotrophin, was demonstrated previously in human breast carcinoma tissues; however, the pattern of pleiotrophin expression in normal breast tissues has not been established. Methods. The expression of pleiotrophin and the related growth factor, midkine, was examined by polymerase chain reaction amplification of reverse transcriptase copies of RNA transcripts (RT‐PCR) from freshly resected n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
94
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(101 citation statements)
references
References 29 publications
5
94
1
1
Order By: Relevance
“…Breast and lung carcinomas, as well as glioblastomas, have different origins. However, these malignant tumor tissues overexpressed MK mRNA, whereas the corresponding noncancerous normal tissues did not (11,12,14). Our results regarding MK mRNA overexpression in thyroid papillary carcinomas coincide with those of the carcinomas originated from the different organs mentioned above.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Breast and lung carcinomas, as well as glioblastomas, have different origins. However, these malignant tumor tissues overexpressed MK mRNA, whereas the corresponding noncancerous normal tissues did not (11,12,14). Our results regarding MK mRNA overexpression in thyroid papillary carcinomas coincide with those of the carcinomas originated from the different organs mentioned above.…”
Section: Discussionsupporting
confidence: 77%
“…In gastric and colorectal carcinomas, the MK mRNA level was higher in cancer specimens than in the corresponding noncancerous tissues (13). Although normal breast and lung tissues did not express MK mRNA, it was frequently expressed in malignant breast and lung tissues (11,12). In our recent study of brain tumors, glioblastomas expressed MK mRNA strongly, although normal brain tissues did not (14).…”
Section: Discussionmentioning
confidence: 90%
“…However, further research is needed to assess the function and mechanism of midkine in the embryonic stem cell culture system. MK expression is up-regulated in the majority of human tumors, including neuroblastomas [44] , head and neck cancer, esophageal cancer, lung cancer [9] , breast cancer [45] , bladder cancer [46] , Wilms' tumor, gastrointestinal cancers [10][11] and a variety of tumor-derived cell lines [9-10, 45, 47, 48] . However, the expression of MK is highly restricted in normal adult tissues, making it a potential marker for cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that expression of midkine (MK) plays an important role in different aspects of tumor progression in diverse solid tumors (6)(7)(8). We have recently shown that high mRNA and protein expression of MK in PDAC protected cancer cells from chemotherapy-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%